The Influence of Work Motivation, commitment, on Teacher Performance - Nur Aini; Ali Idrus; Denny Denmar (Universitas Muhammadiyah Enrekang, 2023)
The aim of this research is to determine the effect of work motivation on teacher performance . The research method is library research. Library research aims to collect data or information in the library and then use it as a basis for research. The research results show that teacher performance is a teacher's ability to carry out learning tasks in madrasas and be responsible for the students under his guidance by improving students' learning achievements. Therefore, teacher performance can be interpreted as a condition that shows a teacher's ability to carry out his duties at the madrasa and describes the actions displayed by the teacher in or during learning activities. Meanwhile, work motivation is energy from within the teacher that provides encouragement to the teacher in carrying out his duties as an educator to achieve educational goals. Teacher work motivation is formed from a teacher's attitude in facing work situations. This motivation can have an influence on a teacher's performance.